2017
DOI: 10.1016/j.jfs.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous market structure and systemic risk: Evidence from dual banking systems

Abstract: This paper investigates how banking system stability is affected when we combine Islamic and conventional finance under the same roof. We compare systemic resilience of three types of banks in six GCC member countries with dual banking systems: fully-fledged Islamic banks (IB), purely conventional banks (CB) and conventional banks with Islamic windows (CBw). We employ market-based systemic risk measures such as MES, SRISK and CoVaR to identify which sector is more vulnerable to a systemic event. We also comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…Some authors attempted to explore relations between different financial tools and systemic risk, such as credit derivative markets, hedge fund, capital network, Shadow Banking, and so on. Abedifar, Giudici, and Hashem (2017) found that the conventional banks with Islamic windows have the least resilient sector under systemic risk attack in dual banking systems. Calistru (2012) studied risk management measures for credit derivatives and suggested that the operational efficiency of credit derivative markets may prevent the occurrence of systemic risks.…”
Section: Financial Market Risk and Stability Analysismentioning
confidence: 99%
“…Some authors attempted to explore relations between different financial tools and systemic risk, such as credit derivative markets, hedge fund, capital network, Shadow Banking, and so on. Abedifar, Giudici, and Hashem (2017) found that the conventional banks with Islamic windows have the least resilient sector under systemic risk attack in dual banking systems. Calistru (2012) studied risk management measures for credit derivatives and suggested that the operational efficiency of credit derivative markets may prevent the occurrence of systemic risks.…”
Section: Financial Market Risk and Stability Analysismentioning
confidence: 99%
“…Thus and although Islamic banks have the same governance structures, they are required to operate in a Shariah ‐compliant manner. This creates unique governance structures, as well as raises a new risk called “ Shariah risk” concerning the potential risk of becoming Shariah non‐compliant, which can generate a further financial turmoil and threaten Islamic banks' activities (e.g., cash deposits and withdrawals), and hence damage the banks' reputation (Abedifar, Giudici, & Hashem, 2017; Ashraf, Rizwan, & L'Huillier, 2016; Aysan & Ozturk, 2018; Bitar, Hassan, & Walker, 2017; Chapra & Ahmed, 2002; Grassa, 2015; Hassan & Aliyu, 2018; Safieddine, 2009). Further, Islamic banking has typically been operating with a weaker government oversight, which has led to a number of noticeable Islamic bank failures (e.g., Islas Finance House in Turkey, the Dubai Islamic Bank, the Islamic Investment Companies of Egypt) (Chapra & Ahmed, 2002; Grassa, 2015; Hasan, 2011; Safieddine, 2009).…”
Section: Bcrs Risk Disclosure and Governance Reforms In Mena Banksmentioning
confidence: 99%
“…The model presented in this study could be generalised to the study of contagion among other country specific financial indicators, or to the study of interconnectedness among other types of financial assets, with the limitation that the considered countries and/or assets should be kept constant over time. Examples of such extensions are contained in the papers by Giudici and Parisi (2017), who consider contagion netween country debt/gdp ratios Avdjev et al (2018), who consider contagion among country banking systems, Abedifar et al (2017), who considers contagion among different banking types, and finally Giudici and Abu-Hashish (2018), who consider interconnectedness among bitcoin prices and financial assets.…”
Section: Introductionmentioning
confidence: 99%